Value-Based Branding in Islamic Boarding Schools: Efforts to Maintain Identity in Digitalization Dynamics - Aini, Tsamar Nur; Nugraha, Lukman; Surbakti, Andika Hariyanto; Mundiri, Akmal; Sanjani, M Aqil Fahmi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the value-based branding strategy in Islamic boarding schools as an effort to maintain traditional identity amidst the rapid flow of digitalization and globalization. Although many other educational institutions have implemented digital branding, its application in the context of Islamic boarding schools is still limited. The study employs a qualitative approach, utilizing case studies of two Islamic boarding schools to explore how these institutions integrate traditional Islamic values into their branding strategies through in-depth interviews, observations, and document analysis. The results of the study indicate that Islamic boarding schools have successfully combined values such as sincerity, simplicity, and social benefits in their branding to maintain relevance in the modern era, thereby strengthening character through a balance with digitalization. The findings emphasize the importance of value-based branding strategies as a research contribution in strengthening the position of Islamic boarding schools as moral and spiritual educational institutions. The study's implications suggest that implementing strategies not only enhances the competitiveness of Islamic boarding schools but also strengthens their relationships with local and global communities, thereby supporting the continuity of Islamic boarding school education in the digital era.